2017
DOI: 10.2135/cropsci2016.05.0350
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nitrogen Fertilizer at Heading Stage Improves Rice Quality under Elevated Temperature during Grain‐Filling Stage

Abstract: Abbreviations: CK, no warming without nitrogen fertilizer at heading stage; CK+N, no warming with N fertilizer at heading stage; DP, degree of polymerization; ET, elevated temperature without nitrogen fertilizer at heading stage; ET+N, elevated temperature with nitrogen fertilizer at heading stage; FATE, free-air temperature enhancement; IS, inferior spikelet; NFHS, nitrogen fertilizer at heading stage; RVA, rapid viscosity analyzer; SEM, scanning electron microscopy; SS, superior spikelet; T max , the time to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…Nitrogen application decreased the chalkiness of Shendao 47 at high N rates, but not for Jingyou 586. Decreased chalkiness in response to increasing N rates agrees with the findings of Zhou et al [21], and Dou et al [22]. According to morphological studies [23,24], chalk is a white opaque part formed from compound starch granules that are loosely packed with numerous air spaces.…”
Section: Appearance Qualitysupporting
confidence: 88%
See 2 more Smart Citations
“…Nitrogen application decreased the chalkiness of Shendao 47 at high N rates, but not for Jingyou 586. Decreased chalkiness in response to increasing N rates agrees with the findings of Zhou et al [21], and Dou et al [22]. According to morphological studies [23,24], chalk is a white opaque part formed from compound starch granules that are loosely packed with numerous air spaces.…”
Section: Appearance Qualitysupporting
confidence: 88%
“…According to morphological studies [23,24], chalk is a white opaque part formed from compound starch granules that are loosely packed with numerous air spaces. Numerous studies on chalk occurrence have been performed in the past decades [22,23,25], and the mechanism of chalk formation has mainly been attributed to the accelerated filling rate during the grain-filling period, which results in loosely packed starch granules [26]. In the present study, the effect of N application on the percentage of chalky grains may be relevant to an assimilate deficit.…”
Section: Appearance Qualitymentioning
confidence: 77%
See 1 more Smart Citation
“…Studies on rice reported that high N rates or late‐stage N application produced long amylopectin branches by reducing the activity of starch branching enzymes. However, another study showed that the distribution of amylopectin chain length was unaffected by N application rates . Although N application rates did not affect starch structure under favorable conditions, high N rates under water deficit conditions increased the proportion of short amylopectin branches in barley .…”
Section: Resultsmentioning
confidence: 97%
“…To reveal the filling characteristics of superior and inferior grains, previous studies have been conducted on plant hormones, enzymes related to grain filling, substance metabolism in the endosperm and starch structure, proteomics, and gene expression differences between superior and inferior paddy rice grains (Nakamura, Yuki, Park, & Ohya, 1989;Nakamura & Yuki, 1992;Xie, Yang, Wang, & Zhu, 2001;Yang, Zhang, Wang, Zhu, & Wang, 2001;Yang, Cao, Zhang, Liu, & Zhang, 2008;Qin, Wang, Hu, & Li, 2010;Wang, Xu, Wang, Yang, & Zhang, 2012;Dong et al, 2014;Zhang et al, 2016;Anyaoha et al, 2018). Researchers also clarified the effects of the sowing date, temperature, light, water management, and nitrogen, and its combination on grain-filling characteristics and rice quality (Dou et al, 2017;Huang et al, 2019;Lin et al, 2010;Sun et al, 2015;Wang et al, 2012;Wei et al, 2018;Yin et al, 2013;Zhang et al, 2012). All of the above studies examined grain filling and the quality of paddy rice.…”
mentioning
confidence: 99%